Dialogical Integration of Life Experiences and Successful Aging. (June 2021) - Filip, Miroslav; Poláčková Šolcová, Iva; Kovářová, Marie; Lukavská, Kateřina; Hofer, Jan; Čermák, Ivo
This article examines the hypothesis that the dialogical integration of life experiences is related to successful aging. Life story interviews with 93 older Czech adults were sorted into categories characterized by specific patterns of life experience integration: (i) without dialogical processes, (ii) with differentiated I-positions, (iii) with dialogical relationships, (iv) partially integrated, and (v) completely integrated. The results indicated that the categories were ordered, yielding low-level correlations with scales of successful aging in predicted directions. A comparison of the categories revealed that they were related to successful aging in a cumulative way, starting with the most essential indicator (lower scores of rumination) in the participants who had developed at least dialogical relationships, continuing to higher well-being linked with partial integration, and ending with an advanced indicator (optimism toward future) linked with complete integration. These relationships were summarized in a hypothetical model that is open to further examination.